Gulf solar energy: Turning plans into reality. Issue 5 (December 2015) - Kalkman, Jaap; Anees, Sameer; Merhaba, Adnan; Bose, Samrat
Abstract : Solar energy is seen as a key way to meet the growing energy demands of emerging countries, and the Gulf states are no exception. But despite grand plans, little has so far been achieved. In this article, the team at consultancy Arthur D. Little discuss how to renew the lost momentum – Part II of the Renewables in the Middle East series.